Given:

Multiply both the sides by 5 we get,

\(\dfrac{ (2x – 2)}{5} × 5 ≤ \dfrac{(6 + 3x)}{7} × 5\)

2x – 2 ≤ 5(6 + 3x)/7

7 (2x – 2) ≤ 5 (6 + 3x)

14x – 14 ≤ 30 + 15x

14x – 14 + 14 ≤ 30 + 15x + 14

14x ≤ 44 + 15x

14x – 44 ≤ 44 + 15x – 44

14x – 44 ≤ 15x

15x ≥ 14x – 44

15x – 14x ≥ 14x – 44 – 14x

x ≥ –44

The solution of the given inequation is (–44, ∞).

Answered by Aaryan | 1 year agoSolve each of the following in equations and represent the solution set on the number line \( \dfrac{5x}{4}-\dfrac{4x-1}{3}>1,\) where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line.\( \dfrac{5x-8}{3}\geq \dfrac{4x-7}{2}\), where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line. 3 – 2x ≥ 4x – 9, where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line. 3x – 4 > x + 6, where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line. 5x + 2 < 17, where

**(i) **x ϵ Z,

**(ii)** x ϵ R.